Memory problems at work: Their range frequency, and severity - Sellen, Abigail; Eldridge, Margery; Bekerian, D (RXRC Cambridge Technical Report, 1992)
This paper reports the results of two studies carried out on memory problems at work. The first study used a diary method to collect a corpus of memory problems. A taxonomy of memory problems was developed and implications for technological support for memory at work are discussed. The second study used a “Memory Lapse Questionnaire” to assess the relative frequencies and severities of various memory problems at work. The results of this questionnaire are reported and implications for the AIR project and its current programme of research are discussed.